2021
DOI: 10.1186/s12974-021-02099-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β mediates alterations in mitochondrial fusion/fission proteins and memory impairment induced by amyloid-β oligomers

Abstract: Background The lack of effective treatments for Alzheimer’s disease (AD) reflects an incomplete understanding of disease mechanisms. Alterations in proteins involved in mitochondrial dynamics, an essential process for mitochondrial integrity and function, have been reported in AD brains. Impaired mitochondrial dynamics causes mitochondrial dysfunction and has been associated with cognitive impairment in AD. Here, we investigated a possible link between pro-inflammatory interleukin-1 (IL-1), mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 89 publications
0
25
0
Order By: Relevance
“…Additionally, mitochondrial trafficking within the cell—for example, for cell membrane repair [ 46 ]—depends on fission. Alterations of mitochondrial dynamics are suspected to be involved in the neurodegenerative process and have been demonstrated in models for all major neurodegenerative diseases, including AD [ 47 ] and PD [ 48 ]. Missense mutations in proteins involved in mitochondrial dynamics, furthermore, are associated with parkinsonism and dementias, such as AD [ 49 ].…”
Section: Mitochondrial Dysfunction In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Additionally, mitochondrial trafficking within the cell—for example, for cell membrane repair [ 46 ]—depends on fission. Alterations of mitochondrial dynamics are suspected to be involved in the neurodegenerative process and have been demonstrated in models for all major neurodegenerative diseases, including AD [ 47 ] and PD [ 48 ]. Missense mutations in proteins involved in mitochondrial dynamics, furthermore, are associated with parkinsonism and dementias, such as AD [ 49 ].…”
Section: Mitochondrial Dysfunction In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Mitochondrial fission often results in dysfunctional and fragmented mitochondria and the balance between fission and fusion is regulated by fusion proteins, including mitofusin 1 (Mfn1) and 2 (Mfn2), and optic atrophy 1 (OPA-1), and fission proteins, such as dynamin-1-like protein (DRP-1) and mitochondrial fission 1 protein (Fis1). In cynomolgus macaques, the expression of mitochondrial fusion proteins (Mfn1, Mfn2, and OPA-1) was reduced and the fission protein DRP-1 was increased after ventricular infusion of oligomeric Aβ, indicating disruption of mitochondrial dynamics and induction of fission [ 178 ]. We have recently shown that Ca 2+ -induced mPTP opening in vitro enhances proteolytic cleavage of L-OPA1 leading to accumulation of S-OPA1 [ 179 ], indicating a crosstalk between mPTP opening and mitochondrial dynamics.…”
Section: Vascular Inflammation Mitochondria and Neuroinflammationmentioning
confidence: 99%
“…Notably, there has been a shift from an initial focus on amyloid plaques to a more contemporary view that memory failure in AD is caused by small soluble Aß oligomers acting as synaptotoxins, leading to cognitive impairment [70]. According to recent findings, Aβ oligomers play a key role in AD brain inflammation by activating the pro-inflammatory interleukin-1 (IL-1) receptors that mediate the alteration in levels of mitochondrial fission/fusion proteins, resulting in memory impairment [71].…”
Section: Alzheimer's Diseasementioning
confidence: 99%